Palaeoenvionmental inferences on the Pleistocene deposits of the Charadros River (Rio graben, Western Corinth Gulf, Greece). (10th July 2021) - Tsoni, Maria; Iliopoulos, George; Valavani, Dimitra; Liapi, Eleni; Papadopoulou, Penelope; Stamoulis, Konstaninos; Koukouvelas, Ioannis; Kontopoulos, Nikolaos
Abstract: Rio graben is a region of significant stratigraphic and palaeontological interest where several environmental changes have been recorded during the Quaternary. These changes are a result of active tectonism, related to the well-known rifting process that has been occurring in the geotectonic region of the Corinth-Patras Rift, as well as of the influence of continuous eustatic and climatic changes. Fossil assemblages from Middle to Upper Pleistocene transitional to marine and terrestrial sedimentary sequences located at Sichaena (Rio Graben) on the west side of Charadros river in NW Peloponnesus, Greece, are analyzed herein in order to distinguish tectonic and eustatic controls. The name of the studied section is Vigla 1 (50 m thickness), belonging to the NE-trending Rio graben, a structure bridging the Corinth graben to the east and the Patras graben to the west. The presence of two normal antithetic second order faults and an unconformity were identified separating the studied stratigraphic section into four distinct sedimentological sequences. The purpose of this work is to determine the palaeoenvironmental conditions of the studied section and to unravel the Middle-Late Pleistocene palaeoenvironmental changes. The micro-fauna evidences oligohaline lagoon sediments at the lower sequence (Sequence 1). Conversely, at the middle (Sequence 2) and at the upper sequence (Sequence 3), the recorded species indicate lagoonal to shallow marine depositional environments. At the top of the section, an unconformity brings into contact Sequence 3 with a sequence consisting a red conglomerate (Sequence 4) that indicates an alluvial fan environment. In order to constrain chronologically the sediments Optically Stimulated Luminescence (OSL) dating was applied. According to the OSL dating results, an Upper Middle Pleistocene age has been attributed for the studied sequences. Moreover, projecting the dating results to the marine isotope curve, a high degree of consistency can be seen between the OSL ages and MIS 7e, 7c and 6d, where the transition from lagoonal facies to shallow marine alternations in sequence 2 correlates well with the MIS 7c highstand, and sequence 3 with MIS 7e and the MIS 6d low stand. Thus, our results indicate the spatial palaeoenvironmental evolution of the studied area which during the Upper Middle Pleistocene is characterised by intense local tectonic movements in conjunction with eustatic sea level changes.